The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1104/pp.79.1.118
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Tobacco Cells to NaCl

Abstract: Cell lines of tobacco (Nicotiana tabacum L. var Wisconsin 38) were obtained which are adapted to grow in media with varying concentrations of NaCI, up to 35 grams per liter (599 millimolar).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
121
0
7

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 160 publications
(135 citation statements)
references
References 40 publications
5
121
0
7
Order By: Relevance
“…In plants, salt stress increases [Ca 2ϩ ] cyt that is presumed to facilitate adaptation (46, 47). Furthermore, plants or cultured cells that are exposed to sublethal levels of salt acquire greater stress adaptive capacity (48,49), and tomato seedlings subjected to hyperosmotic pretreatment exhibit enhanced salt tolerance (50). The results of this study provide direct evidence that hyperosmotic stress, generated by salt or a non-ionic osmotic solute, induces a transient [Ca 2ϩ ] cyt increase in yeast cells, and this [Ca 2ϩ ] cyt transient mediates ionic but not osmotic stress adaptation.…”
Section: Transient Increase In Ca Cytmentioning
confidence: 49%
“…In plants, salt stress increases [Ca 2ϩ ] cyt that is presumed to facilitate adaptation (46, 47). Furthermore, plants or cultured cells that are exposed to sublethal levels of salt acquire greater stress adaptive capacity (48,49), and tomato seedlings subjected to hyperosmotic pretreatment exhibit enhanced salt tolerance (50). The results of this study provide direct evidence that hyperosmotic stress, generated by salt or a non-ionic osmotic solute, induces a transient [Ca 2ϩ ] cyt increase in yeast cells, and this [Ca 2ϩ ] cyt transient mediates ionic but not osmotic stress adaptation.…”
Section: Transient Increase In Ca Cytmentioning
confidence: 49%
“…Cell suspensions of Nicotiana tabacum L. var Wisconsin 38, adapted to different concentrations of NaCl (up to 600 mM), were maintained according to procedures described previously (1). Unadapted 7 ,um in diameter, at an accelerating voltage of 10 kV the limits of resolution are estimated to be 2-3,m [18]), and a relatively even surface across the cell so that the topography at the various points of analysis would be consistent.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously characterized the growth and osmotic adjustment of Nicotiana tabacum L. var Wisconsin 38 cells (1) adapted to high levels of salinity (428 mm NaCI). Na+ and Cl-, the principal components of the extensive osmotic adjustment exhibited by these cells, accumulated to an average whole cell concentration of 500 and 400 mm, respectively (2).…”
mentioning
confidence: 99%
“…We have previously shown that cells adapted to near sea water levels of salinity (428 mm NaCI) accumulate high concentrations of Na+ and Cl1 and compartmentalize these ions in the vacuole (2,4). The tonoplast H+-ATPase from these cells exhibited a higher specific H+-transport capacity and ATPase activity than the tonoplast ATPase isolated from unadapted cells (26).…”
mentioning
confidence: 96%